Etiology of Genital Ulcer Disease in a Sexually Transmitted Infection Reference Center in Manaus, Brazilian Amazon - Gomes Naveca, Felipe (Public Library of Science, 2013)
OBJECTIVES: To determine the etiology and factors associated with genital ulcer disease (GUD) among patients presenting to a sexually transmitted infections clinic in Manaus, Brazil; and to compare a multiplex polymerase chain reaction (M-PCR) assay for the diagnosis of GUD with standard methods. METHODS: Ulcer swabs were collected and used for Tzanck test and processed in an M-PCR to detect herpes simplex virus (HSV-1/2), Treponema pallidum (T. pallidum), and Haemophilus ducreyi (H. ducreyi). Sera were tested for HIV and syphilis antibodies. Multivariable analysis was used to measure the association between clinical aspects and GUD. M-PCR results were compared with syphilis serology and Tzanck tests. RESULTS: Overall, 434 GUD samples were evaluated, 84.8% from men. DNA from HSV-2 was detected in 55.3% of GUD samples, T. pallidum in 8.3%, HSV-1 in 3.2%, and 32.5% of GUD specimens were negative for the DNA of all three pathogens. No cases of H. ducreyi were identified. HIV serology among GUD patients was 3.2%. Treponemal antibodies and Tzanck test positivity for genital herpes was detected in 25 (5.8%) and in 125 (30.3%) of GUD patients, respectively. In multivariable analysis genital herpes etiology by M-PCR was associated with the vesicular, multiple and recurrent lesions whereas T. pallidum with non-vesicular, non-recurrent lesions. Compared to M-PCR, syphilis serology was 27.8% sensitive and 96.2% specific whereas Tzanck test was 43.8% sensitive and 88.9% specific. CONCLUSIONS: The predominance of genital herpes etiology suggests a revision of existing national syndromic treatment guidelines in Brazil to include antiherpetic treatment for all GUD patients. The use of M-PCR can significantly improve the diagnosis of GUD and provide a greater sensitivity than standard diagnostics.